What Matters for Environmental Quality in the Next-11 Countries: Economic Growth or Income Inequality? - Hemachandra Padhan; Ilham Haouas; Bhagaban Sahoo; Almas Heshmati (Institute of Labor Economics (IZA), 2018)
This study uses 1971-2013 panel data to explore the implications of growth, wealth disparities and energy consumption on carbon emissions in a sample of Next-Eleven (N-11) countries. It uses modern econometric techniques to highlight a long-run interplay between selected variables in the carbon emissions function for all the N-11 nations and long-run interactions among the series analyzed. Contrastingly, it also shows that economic growth, income inequalities and energy consumption accelerate CO2 emissions. In addition to examining the effects of the wealth disparities square, the study also uses the Environmental Kuznets Curve hypothesis in the context of the N-11 states. Its findings suggest that policymakers should curb rising income inequalities through effective redistributive measures such as tax transfers (cash transfers) and taking up other expenditure programs for the poor. Moreover, the Indian government should emphasize on an energy-reducing strategy policy to reduce income inequalities and achieve sustainable development.
Keywords: Q50; O15; C23; 330; CO2 emissions; income inequality; panel cointegration; Next-Eleven countries